Demagnetisation fault analysis and diagnosis based on different methods in permanent magnet machines ‐ An overview - Jawad Faiz; Mohammad Amin Bazrafshan; Zabihollah Tabarniarami (IET Electric Power Applications)
Abstract The expansion of permanent magnet (PM) machines due to functional advantages such as power density and low losses (high efficiency) and better controllability in industrial applications has led to an increased need for research on possible faults in this type of machine and the development of effective methods to diagnose faults in different operational conditions. The performance characteristics of PM machines are strongly influenced by the PMs used in their structure. Accordingly, one of the most important PM machine faults is the demagnetisation fault which arises due to the physical, operational, and environmental conditions or their combination. This can result in damage to the functional characteristics of the machine. In this paper, the main topologies of PM machines, including the PM synchronous machines, the brushless DC motors, and the flux modulation machines, are first reviewed. Subsequently, the techniques for detecting demagnetisation faults in PM machines are then reviewed and summarised. This paper discusses the factors that cause faults in PM machines and their effects on machine performance. It also examines conventional modelling methods used to study demagnetisation faults. Finally, it presents a general structure for techniques developed for demagnetisation faults in different operating conditions (stationary and non‐stationary) and based on intelligent methods. It also compares the proposed methods and highlights their strengths and weaknesses.